Hospital disinfectant efficacy testing: Experimental evidence towards the requirement of common international regulatory framework, the case of Costa Rica - Delgado Rodríguez, Fabián Vinicio (2023)
Background: Costa Rica, as many developing countries around the world, lacks a specific regulatory framework for hospital disinfectant efficacy testing. The aim of this study is to evaluate the efficacy of disinfectant samples used in healthcare facilities of Costa Rica to provide experimental evidence to encourage the definition of public health polices in this matter. Methods: The determination of efficacy for disinfectant samples were based on Association of Official Agricultural Chemists (AOAC) use-dilution methods 955.15 (Staphylococcus aureus ATCC 6538) and 964.02 (Pseudomonas aeruginosa ATCC 15442) with minor modifications. Results: Ineffective disinfectant samples intended for their use in healthcare centers were identified. Experimental data indicates that disinfectants tested have lower activity against Gram-negative bacteria than Gram-positive bacteria. Conclusions: Despite most analyzed disinfectant samples are effective, there are products that did not satisfy performance criteria. The study gives experimental data that are useful to encourage the definition of a regulatory frame for hospital disinfectant efficacy testing in Costa Rica.